Dismal Employment Growth in EU Countries : The Role of Corporate Balance Sheet Repair and Dual Labor Markets - Bakker, Bas (IMF Working Papers; Working Paper ;, 2013)
This paper argues that the large differences among EU countries in post-crisis employment performance are to a large extent driven by the need to adjust corporate balance sheets, which had greatly deteriorated during the boom years in some countries but not in others. To close the large gaps between saving and investment, firms reduced investment and cut costs to boost profits. With much of the cost adjustment falling on firms' wage bills, employment losses were largest in countries under the most intense pressures to improve corporate profitability and with limited wage flexibility due to labor market duality.